THE EFFECT OF KNOWLEDGE, PROMOTION, SERVICE AND PROFIT SHARING ON MEMBERS' INTEREST IN USING STUDENT SAVINGS PRODUCTS OF KSPPS MUI JATIM - Yaqin, Muhammad Ainul; Fahim, Achmad; Ya'qub, Moh (JURNAL PROFIT, 2025)
This research aims to analyze the influence of knowledge, promotion, service, and profit-sharing on members' interest in using Student Savings Account products of KSPPS MUI JATIM Sidayu Branch in Mriyunan Village, Sidayu, Gresik. The research method used is quantitative with a descriptive approach. Data collection was conducted through questionnaires distributed to 100 respondents who are members of KSPPS MUI JATIM Sidayu Branch residing in Mriyunan Village, Sidayu, Gresik. The data analysis technique used multiple linear regression analysis with SPSS software. The findings indicate that all four factors—knowledge, promotion, service quality, and profit-sharing—collectively have a meaningful impact on members' interest in using the product. Individually, each factor also shows a positive and significant influence. Among them, promotion emerged as the most influential factor in encouraging member participation. This research provides implications for KSPPS MUI JATIM Sidayu Branch to enhance their marketing strategy by focusing on improving service quality, educating the community about their products, developing attractive promotional programs, and establishing competitive profit-sharing arrangements to increase members' interest in using Student Savings Account products.